Data for molecular recognition between polyamide thin film composite on the polymeric subtract by molecular dynamic - Wan Zulaisa Amira, Wan Jusoh; Sunarti, Abd Rahman; Abdul Latif, Ahmad; Nadzirah, Mohd Mokhtar (Elsevier, 2019)
This paper focus to examine the best molecular interaction between Polyamide Thin Film Composite (PA TFC) layers with different properties of the support membrane. The support membrane of Nylon 66 (N66) and Polyvinylidene fluoride (PVDF) was chosen to represent the hydrophilic and hydrophobic model respectively in the Molecular Dynamic (MD) simulation. The Condensed-Phase Optimized Molecular Potential for Atomistic Simulation Studies (COMPASS) force field was used with the total simulation runs were set 1000 picoseconds run production ensembles. The temperature and pressure set for both ensembles were 298 K and 1 atm respectively. The validity of our model densities data was check and calculated where the deviation must be less than 6%. The comparison between hydrophobic and hydrophilic of the support membrane data was examined by the distance and magnitude of intensity of the Radial Distribution Function (RDF's) trends.